2016
DOI: 10.15376/biores.11.3.6393-6406
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-Compatible Purified Endoglucanase from the Agro-Industrial Residue by Trichoderma harzianum under Solid State Fermentation

Abstract: A robust process of purification, characterization, and application of endoglucanase from the agro-industrial waste was performed using solid state fermentation (SSF). Trichoderma harzianum as a micro-organism and wheat straw as a growth supportive substrate were used in SSF under pre-optimized conditions. The maximum activity of 480 ± 4.22 U/mL of endoglucanase was attained when a fermentation medium was inoculated using 10% inoculum size and 3% substrate concentration with pH = 5.5 at 35 °C for an optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…To do one-step purification and immobilisation, three strategies are used: (i) immobilisation at one point, (ii) use of specially synthesised supports for specific binding, and (iii) use of directed mutagenesis to increase the affinity of target protein towards the supports [197]. Solid-state fermentation is a promising way to produce industrially important bacteria in a high amount with low manufacturing costs [198,199]. Because of their friendly nature with the solid-state fermentation process conditions, Basidiomycetes fungi are commonly used to synthesise most of the industrial enzymes [200,201].…”
Section: Enzymes and Lipidsmentioning
confidence: 99%
“…To do one-step purification and immobilisation, three strategies are used: (i) immobilisation at one point, (ii) use of specially synthesised supports for specific binding, and (iii) use of directed mutagenesis to increase the affinity of target protein towards the supports [197]. Solid-state fermentation is a promising way to produce industrially important bacteria in a high amount with low manufacturing costs [198,199]. Because of their friendly nature with the solid-state fermentation process conditions, Basidiomycetes fungi are commonly used to synthesise most of the industrial enzymes [200,201].…”
Section: Enzymes and Lipidsmentioning
confidence: 99%
“…by SSF which proved to be quite stable when incubated in the acid to basic pH range, with an optimum pH of 6.5. In the study carried out by Ahmed et al (2011), A. niger proteases showed a range of enzymatic stability between pH 5.0 and 8.0, with the highest activity at pH 7.0. Madhumithah et al (2011) obtained higher protease activities when the residues were at pH 6.0 when using various plant residues for the production of proteases by SSF from the fungus A. niger.…”
Section: Optimal Ph and Stability At Different Phs Of The Crude Enzym...mentioning
confidence: 99%
“…Bits of white cloth were tainted with locally obtainable permanent blue ink and the pieces were then immersed into disinfected enzyme mixed detergent solution and detergent solution without enzymes. The de-staining ability was tested after standard incubation time (10-15 minutes) at 50 o C and subsequently being washed twice with water (21).…”
Section: De-staining Abilitymentioning
confidence: 99%
“…This suggests that the enzyme may be useful to the detergent and laundry industries as a suitable additive to detergents for improved washing and maintenance of the fabric quality. Ahmed, et al (21) showed that enzyme mixed with detergent solution entirely removed ink stain present on the white cloth, while with the detergent only left a spot.…”
Section: De-staining Abilitymentioning
confidence: 99%